Effect of pefloxacin on certain natural host defence mechanisms and immune response in rabbits - Jose, Sweety; Honnegowda, Honnegowda; Jayakumar, K; Krishnappa, G; Narayana, K (The Indian Journal of Animal Sciences, 2012)
Pefloxacin was given @ 6mg/kg twice daily far 5 days with or without Brucella-plain killed antigen to study the natural non-specific host defence mechanisms and specific immune response. Among the different parameters assessed, the agglutinating antibody titres and the absolute lymphocyte count were reduced slightly by pefloxacin, but it was not significant. The total immunoglobulin concentration, total serum protein and total leukoeyte count were not affected. The cell-mediated immunity was also not affected by pefloxacin. Hence, the natural host defence mechanisms and cell-mediated immunity were not affected by pefloxacin, but the humoral immune response was reduced slightly, though not significantly.